2010
DOI: 10.1002/hep.23641
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignant Neoplasms of Liver and Biliary Tract in Diabetic Patients With Different Age and Sex Stratifications

Abstract: We prospectively investigated 615,532 diabetic patients and 614,871 age-matched and sexmatched control subjects selected from National Health Insurance claims for malignant neoplasms of liver and biliary tract (International Statistical Classification of Diseases and Related Health Problems, 9th edition, codes 155 and 156, respectively) between 2000 and 2006. The person-year approach with Poisson assumption was used to estimate the hazard rates. We also evaluated the age-specific and sex-specific relative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 37 publications
3
78
1
Order By: Relevance
“…These 13 cohort studies had a median duration of follow-up of 10 years (range: 2.3-20 years), reporting a total of 2,493 incident cases of BTC or cancer of its subsites. The methods of DM ascertainment were on the basis of self-reported history of DM or blood glucose levels test in most studies, except for two studies in which the ascertainment of DM was based on registry of disease [26,27]. The ascertainment of outcome was based on cancer registry in all studies, with the exception of one study in which GBC diagnosis was made by histological evaluation [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 13 cohort studies had a median duration of follow-up of 10 years (range: 2.3-20 years), reporting a total of 2,493 incident cases of BTC or cancer of its subsites. The methods of DM ascertainment were on the basis of self-reported history of DM or blood glucose levels test in most studies, except for two studies in which the ascertainment of DM was based on registry of disease [26,27]. The ascertainment of outcome was based on cancer registry in all studies, with the exception of one study in which GBC diagnosis was made by histological evaluation [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We identified two case-control studies [21,23] and seven cohort studies [27,[29][30][31][32][33][34] that presented results on diabetes and risk of biliary tract cancer. Another diabetic cohort study reported results with SMR [15].…”
Section: Diabetes and Risk Of Btcmentioning
confidence: 99%
“…We first identified patients with a diagnosis of CRC (ICD-9-CM codes 153.0 to 153.9 and 154.0 to 154.2) from inpatient and outpatient claims during the study period. These CRC patients must also have been issued catastrophic illness certificates that further ensure the accuracy of cancer diagnosis (21). To ensure the inclusion of only newly diagnosed CRC between 2000 and 2010, patients who had a diagnosis of CRC between 1995 and 1999 were excluded.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…False reports of diagnosis would yield a severe penalty from the BNHI (20). Therefore, information obtained from the NHIRD is considered to be complete and accurate (21). The NHIRD provided information on encrypted patient identification numbers, sex, birthday, dates of admission and discharge, medical institutions providing the services, the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes of up to five diagnoses and procedures, respectively, outcome at hospital discharge (recovered, died or transferred out), order codes and the fees charged for medical services.…”
Section: Source Of Datamentioning
confidence: 99%
“…The geographic location of each individual's NHI unit-either near the location of employment or residential area-was classified under north, central, south, or east and under either of the following urbanization statuses-urban or rural-as per the National Statistics of Regional Standard Classification (Chen et al 2010).…”
Section: Discussionmentioning
confidence: 99%